A palace for a Hero: The Imperial Holy Palace of Constantinople in "Tirant lo Blanc" - Teresa Izquierdo Aranda (Anales de Historia del Arte, 2014)
Joannot Martorell recovers the Gran Palacio Imperial de Constantinople in the Greek chapter of Tirant lo Blanch, in order to provide a symbolic space to the heroic projection of his main character. Tirant achieves in the fiction an impossible dream even in reality. Uses the capital of Bosphorus as a symbol for a real New Rome and rescues an enclosure that in the Christian sphere becomes the heir of the ancient Empire. In this article we will analyze with detail the resources employed by Martorell to recreate the palace environment and value the contribution of the literary text as a source for History of Art.